Menos armas, menos crimes - Daniel Ricardo de Castro Cerqueira; Jo\~ao Manoel Pinho de Mello (Instituto de Pesquisa Econômica Aplicada (IPEA), 2012)
– Do more guns cause less crime or more crime? Some authors argue that the spread of firearms encourage violent solutions to interpersonal conflicts. Other authors, however, suggest that the defensive use of gun decreases economic crime. In this paper we proposed an identification strategy to estimate the effect of guns on violent crimes and on property crime. The strategy was based on the use of instrumental variables that allowed us to explore the temporal and cross-section variation of the crimes and prevalence of guns in cities. The instrument was developed based on the Statute of Disarmament (ED) - a national law passed in December 2003. The identification hypothesis is that the impact of ED on the demand for weapons would be greater as higher the prevalence of weapons previous the occurrence of the Law. We presented evidence that the policy of disarmament, operated in the state of S\~ao Paulo between 2001 and 2007, was one of the relevant factors that led to the decrease in violent crime, particularly homicides (average elasticity around 2.0). On the other hand, we found no evidence of any effect on other crimes with economic motivation as larceny, vehicle theft, and trafficking of illicit drugs, suggesting the irrelevance of the potential effect of deterring crime by the armed victim.
Keywords: K42; 330